Laser Cleaning Using Q-Switched Nd:YAG Laser of Low Carbon Steel Alloys - S. N. Ali; Z. A. Taha; T. S. Mansour (Advances in Condensed Matter Physics)
This paper represents the efforts to achieve the laser cleaning process of low carbon steel alloys AISI1005 and AISI1012 with 0.65 mm and 1 mm thickness, respectively. The cleaning experiments were performed with a Q-switched Nd:YAG nanosecond laser at wavelengths of 1064 nm and 532 nm. The parameters that have been selected for the present work are peak power which varies as 5, 15, 30, 40, and 50 MW and pulse repetition rate which varies from 1 to 6 Hz by 1 Hz increment. Effects of these parameters on the microstructure and the mechanical properties of the two alloys have been realized. Also predicted results of analytical model regarding the depth were compared with the experimental results which show a good agreement between both.